To a Mountain in Tibet - Thubron, Colin (London : Vintage Books, 2012)
Offers an intimate travelogue of the author's trek to Kailas, the holiest mountain in Tibet, in the wake of the death of his mother and the loss of his family.
Includes Bibliographical References and Index.
Keywords: China Mount Kailas; China Tibet Autonomous Region; Kailas, Mount (China) Description and travel